(untitled) (Research, Society and Development, 2025)
The main objectives of this study were to identify the coping strategies adopted by family members to deal with the psychological impacts of femicide, to understand the social representations of these family members and also to map the support networks available to this public. This is a mixed study, comprising an integrative literature review, based on the analysis and discussion of the articles found, and an opinion poll, carried out in the municipality of Teresina, capital of Piauí, with 131 participants from Teresina. The results show that the coping strategies identified by the public are similar to those found in the literature, highlighting the importance of psychological support in the family’s bereavement process. These data indicate that this is a growing and urgent issue for public policies that integrate care with legal, social, psychological and community support, with a view to raising awareness of the issue and providing support for families bereaved as a result of the crime of femicide.